2017
DOI: 10.1371/journal.pone.0182530
|View full text |Cite
|
Sign up to set email alerts
|

A CRE1- regulated cluster is responsible for light dependent production of dihydrotrichotetronin in Trichoderma reesei

Abstract: Changing light conditions, caused by the rotation of earth resulting in day and night or growth on the surface or within a substrate, result in considerably altered physiological processes in fungi. For the biotechnological workhorse Trichoderma reesei, regulation of glycoside hydrolase gene expression, especially cellulase expression was shown to be a target of light dependent gene regulation. Analysis of regulatory targets of the carbon catabolite repressor CRE1 under cellulase inducing conditions revealed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
102
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(111 citation statements)
references
References 75 publications
(115 reference statements)
9
102
0
Order By: Relevance
“…We focused on the polyketide trichodimerol (Shirota et al ., ), a fungal metabolite with potential anticancer activity (Serwe et al ., ) and the peptaibol antibiotic paracelsin (Brückner et al ., ) as model substances. Both metabolites were previously shown to be produced in T. reesei (Brückner et al ., ; Monroy et al ., ). The supernatants of cultures were analyzed with quantitative mass spectrometry for known secreted fungal metabolites.…”
Section: Resultsmentioning
confidence: 97%
“…We focused on the polyketide trichodimerol (Shirota et al ., ), a fungal metabolite with potential anticancer activity (Serwe et al ., ) and the peptaibol antibiotic paracelsin (Brückner et al ., ) as model substances. Both metabolites were previously shown to be produced in T. reesei (Brückner et al ., ; Monroy et al ., ). The supernatants of cultures were analyzed with quantitative mass spectrometry for known secreted fungal metabolites.…”
Section: Resultsmentioning
confidence: 97%
“…In previous studies, the ability of T. reesei to produce sorbicillinoids was reported to vary with different carbon sources [ 19 , 37 – 39 ]. To see whether the superior sorbicillinoids’ production of strain ZC121 compared to strain RUT-C30 is dependent on carbon source, both the sorbicillinoids and cellulase production of strains ZC121 were measured during the time course of growth on TMM containing cellulose, lactose, glucose, galactose or glycerol as the individual carbon source (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Other carbon sources, such as lactose, glycerol, and galactose have been reported to be utilized by T. reesei to produce remarkable amounts of sorbicillinoids. Furthermore, the sorbicillinoids’ production in fungi has been reported to be generally impacted by culture conditions, such as carbon source [ 9 , 37 ], light exposure time [ 39 ], temperature, and pH. By contrast, the recombinant strain ZC121 displayed hyperproduction of sorbicillinoids regardless the culture conditions, so long as T. reesei can grow well.…”
Section: Discussionmentioning
confidence: 99%
“…For industrial application of T. reesei , the ability to produce secondary metabolites is of high importance. Recently, connections between primary and secondary metabolism were indeed shown ( 9 , 10 ). Comparison of the genome of T. reesei with the genomes of the potent biocontrol fungi Trichoderma atroviride and Trichoderma virens indicated that at least part of the mycoparasitism-specific gene content was lost in evolution in T. reesei ( 5 , 11 ).…”
Section: Introductionmentioning
confidence: 97%